2020
DOI: 10.1002/bkcs.12065
|View full text |Cite
|
Sign up to set email alerts
|

Balancing All‐Atom Force Field for DNA Simulations Using Osmotic Pressure Data

Abstract: For classical molecular dynamics (MD) simulations of DNA molecules, several all‐atom force fields have been developed, including the very popular amber bsc1 force field. Despite marked improvement from the standard amber99 force field, this force field has a tendency to underestimate base‐pair hydrogen bonds and overestimate base stacking (BS). Previously, the weakened hydrogen bond with the bsc1 was improved by modulating a limited number of van der Waals sigma parameters. In this study, to resolve the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The AMBER bsc1 or OL , ff can be a popular choice for MD simulations of GQs, but these ffs tend to underestimate base pair hydrogen bonds (HBs) , and overestimate stacking interactions between bases. , Furthermore, an enhanced sampling MD simulation using the standard bsc1 ff indicated that the native antiparallel GQ structure of the 15-nt thrombin-binding aptamer (TBA15; two-layered GQ) was not located at the global free energy minimum . To resolve this ff issue, the bsc1 ff was modified by tuning van der Waals (vdW) σ parameters of the base polar atoms (N and O), such that the experimental unfolding free energy value (Δ F N→D ≡ F D – F N = 1.1–3.3 kcal/mol) of TBA15 was reproduced as closely as possible.…”
Section: Introductionmentioning
confidence: 99%
“…The AMBER bsc1 or OL , ff can be a popular choice for MD simulations of GQs, but these ffs tend to underestimate base pair hydrogen bonds (HBs) , and overestimate stacking interactions between bases. , Furthermore, an enhanced sampling MD simulation using the standard bsc1 ff indicated that the native antiparallel GQ structure of the 15-nt thrombin-binding aptamer (TBA15; two-layered GQ) was not located at the global free energy minimum . To resolve this ff issue, the bsc1 ff was modified by tuning van der Waals (vdW) σ parameters of the base polar atoms (N and O), such that the experimental unfolding free energy value (Δ F N→D ≡ F D – F N = 1.1–3.3 kcal/mol) of TBA15 was reproduced as closely as possible.…”
Section: Introductionmentioning
confidence: 99%